Aplicação de sistema combinado: lodos ativados e foto-Fenton solar para remoção da atividade estrogênica de 17á-etinilestradiol e estrona - Nicole Hastenreiter Rocha (2017)
Estrogens have been detected in surface water, groundwater, drinking water and wastewater. Several deleterious effects resulting from exposure of humans and other animals to these compounds have been reported in the literature. Estrone (E1), a natural estrogen, and synthetic 17-ethinylestradiol (EE2) are recognized as the main contributors to sanitary wastewater estrogenicity. However, biological treatments, which are commonly applied in urban wastewater treatment plants, do not achieve the proper removal of estrogenic activity. Therefore, tertiary treatments that address this flaw have been intensively studied, as is the case of Advanced Oxidative Processes (AOPs). In the present study, the applicability of activated sludge and its combination with an AOP, solar photo-Fenton, were tested for the removal of estrogenic activity of a synthetic domestic wastewater spiked with E1 and EE2. Wastewater and effluents from both treatment routes were analyzed for estrogenic activity and toxicity, through the YES test and Microtox® (Allivibrio fischeri), respectively. Activated sludge system alone presented 83% removal of estrogenic activity, showing a residual EQ-E2 of 1370 ng.L-1. Toxicity of synthetic sanitary sewage was also removed after biological treatment. For the solar photo-Fenton assays, two types of semi-pilot reactors were tested, the Composite Parabolic Collector (CPC) and the Raceway Pond Reactos (RPR). In both reactors, experiments were carried out following a factorial design so that different concentrations of H2O2 and Fe2+ were tested. Regarding the removal of estrogenic activity, the two reactors presented similar behavior and removals were superior to 96% within the first 5 minutes of reaction. Best removal rates, 99.7% for CPC and 98.9% for RPR, were obtained when using 60 mg.L-1 of Fe2+ and 350 mg.L1 of H2O2.. Lowest values of toxicity were reached for reactions conducted in the RPR, and toxicity was completely removed when highest concentrations of both reagents were used in this reactor (100 mg.L-1 of Fe2+ and 500 mg.L-1 of H2O2)